Enteric fever resembling Malawi-Mozambique outbreak - Xavier, Rose M.; Roni, Ajith; Legha, R. (International Journal of Research in Medical Sciences, 2023)
A 47-year-old male with no known co-morbidities presented with hematochezia and multiple episodes of vomiting. He had a history of high-grade fever with chills, rigor, vomiting, and abdominal pain 3 weeks ago, for which he was treated with 5 days of IV antibiotics in another hospital. Examination revealed tremor, rigidity, hyperreflexia, bradykinesia, and hypophonic monotonous speech. Colonoscopy showed ileocolonic ulcers. Widal came positive. Treated as a case of Enteric fever with neurological complications such as parkinsonism, UMN signs, and gastrointestinal bleeding secondary to an ileal ulcer.